2011
DOI: 10.3174/ajnr.a2575
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Sinus Stenting for Idiopathic Intracranial Hypertension: A Review of 52 Patients and of Model Predictions

Abstract: BACKGROUND AND PURPOSE:Transverse sinus stenosis is common in patients with IIH. While the role of transverse sinus stenosis in IIH pathogenesis remains controversial, modeling studies suggest that stent placement within a transverse sinus stenosis with a significant pressure gradient should decrease cerebral venous pressure, improve CSF resorption in the venous system, and thereby reduce intracranial (CSF) pressure, improving the symptoms of IIH and reducing papilledema. We aimed to determine if IIH could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
330
1
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(357 citation statements)
references
References 47 publications
11
330
1
15
Order By: Relevance
“…The benefit of venous stenting in PTC is now clear, [1][2][3] and a lower complication rate (9.3% of patients in our own study) compared with shunting has been reported in all studies. We have now shown that the cost of stenting is also significantly less than that of shunting.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The benefit of venous stenting in PTC is now clear, [1][2][3] and a lower complication rate (9.3% of patients in our own study) compared with shunting has been reported in all studies. We have now shown that the cost of stenting is also significantly less than that of shunting.…”
Section: Discussionmentioning
confidence: 83%
“…In some cases, the entire transverse sinus has been stented. 1 Given this significant difference in the repeat rates of the 2 procedures, the cost per 100 cases does not represent the total longer term cost per patient of ongoing revisions. Because the venous stent group was followed up to 12 years, it is reasonable to view the absolute number of repeat procedures as representative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 A pivotal question regarding transverse sinus stenosis in IIH is whether this abnormality is the cause or consequence of the elevated intracranial pressure. 21 Mathematical models support the hypothesis that the transverse sinus is a compliant structure to the point of being vulnerable to extrinsic compression, which may obstruct the venous drainage, resulting in venous and intracranial hypertension. 24 On the other hand, results published in recent years, which show clinical improvement in some patients after the reconstruction of the transverse sinus with endovascular stents, reinforce the hypothesis that the stenosis established in the sinus independently causes the venous flow blockage.…”
Section: Discussionmentioning
confidence: 84%